Induced-volatolomics, a new research field in chemical biology - Blochouse, Estelle; Eid, Rony; Cannoni, Elsa; Châtre, Rémi; Geffroy, Claude; Opalinski, Isabelle; Papot, Sébastien; Poinot, Pauline (Comptes Rendus. Chimie, 2024)
Progresses in chemical biology have substantially deepened our understanding of biological pathways related to disease outcomes. Numerous optical probes activatable by disease-relevant enzymes have been designed and have shown great value for imaging crucial biochemical transformations specific to pathological processes. In comparison to their “always-on” counterparts, such stimuli-responsive probes stand out as promising candidates for exploring biological processes because of their high sensitivity, ingenious spatiotemporal resolution, ease of operation, and real-time and in situ imaging capacity. However, these imaging tools meet several bottlenecks related to either stability, background noise, limited penetration depth or systemic toxicity, pharmacokinetics, tissue distribution, and renal clearance.In parallel, novel volatile organic compound (VOC)-based probes have been proposed under the emerging paradigm of induced-volatolomics. These probes are converted into exogenous VOCs in response to pathogen or eukaryote specific enzymatic stimuli. Once activated, VOC-based probes release volatile tracers that inform the biochemical processes arising in cells, liquid and solid biopsies, and even in entire organisms. After a brief presentation of recent developments in the field of induced-volatolomics, we discuss possible improvements of this new modality for the exploration of biological systems.